KARAPANDZIC FLAP AND BERNARD-BURROW-WEBSTER FLAP FOR RECONSTRUCTION OF LOWER LIP - Ana Brinca; P. Andrade; Ricardo Vieira; Américo Figueiredo (Journal of the Portuguese Society of Dermatology and Venereology, 2011)
Squamous cell carcinoma is the most common malignant neoplasm of the lips, and in about 90% of cases it’s located in the lower lip due to the higher cumulative exposure to ultraviolet radiation. The authors present two surgical techniques for reconstruction of large lower lip defects, resulting from tumor surgical excision, exemplifying and comparing them with two clinical cases.